2015
DOI: 10.11648/j.sjph.20150303.15
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Anxiety and Academic Performance of Postgraduate International Students in a British University: A Cross-Sectional Quantitative Design

Abstract: Aims: Anxiety has a great effect on students' academic performance, especially among international students. Acculturation, discrimination, familiarity with the education system, weather, social support, and language limitation are among the main factors which contribute to anxiety among international students. This small scale study assesses the relationship between anxiety and academic performance of international students among postgraduate international students of in the University of Bedfordshire. A cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Consistent with previous studies [36,37], findings from baseline data supported a negative relationship between symptoms of anxiety and academic performance among university students. Moreover, students meeting the criteria for possible generalized anxiety disorder (GAD) had lower GPA scores compared to students in the Non-GAD group.…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with previous studies [36,37], findings from baseline data supported a negative relationship between symptoms of anxiety and academic performance among university students. Moreover, students meeting the criteria for possible generalized anxiety disorder (GAD) had lower GPA scores compared to students in the Non-GAD group.…”
Section: Discussionsupporting
confidence: 88%
“…Findings showed that anxiety was significantly correlated to academic performance. The results showed that workload, choice of coping with stress, future prospects, and change in the system of education are the major types of anxiety affecting participants, giving significant relationships when cross-tabulated with gender and ethnicity (35). (36) investigated college students' procrastination and suggested countermeasures that students or administrators could use as strategies to reduce delay.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Others have shown that financial stress is related to academic performance. Adeoye-Agboola and Evans (2015) in their study found that anxiety or stress could influence students on their academic performance through their financials. Moreover, financial factors may also contribute to psychological distress of university students regardless of gender (Vasugi & Hassan, 2019).…”
Section: Social Relationship During Covid-19 Pandemicmentioning
confidence: 97%